If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + (x + 9) + (x + 6) = 207 Reorder the terms: X + (9 + x) + (x + 6) = 207 Remove parenthesis around (9 + x) X + 9 + x + (x + 6) = 207 Reorder the terms: X + 9 + x + (6 + x) = 207 Remove parenthesis around (6 + x) X + 9 + x + 6 + x = 207 Reorder the terms: 9 + 6 + X + x + x = 207 Combine like terms: 9 + 6 = 15 15 + X + x + x = 207 Combine like terms: x + x = 2x 15 + X + 2x = 207 Solving 15 + X + 2x = 207 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + X + -15 + 2x = 207 + -15 Reorder the terms: 15 + -15 + X + 2x = 207 + -15 Combine like terms: 15 + -15 = 0 0 + X + 2x = 207 + -15 X + 2x = 207 + -15 Combine like terms: 207 + -15 = 192 X + 2x = 192 Add '-2x' to each side of the equation. X + 2x + -2x = 192 + -2x Combine like terms: 2x + -2x = 0 X + 0 = 192 + -2x X = 192 + -2x Simplifying X = 192 + -2x
| -2x-6=-6x+-2 | | 3(4x-2)=9+2x+5 | | 3-q/4=18 | | 3a-12= | | 130/n=65/100 | | 3x+4=51 | | 12x-18=36-15x | | ln(x+4)-ln(x-5)=3 | | a(7b-2c)= | | 4x+10y=3000 | | 250x^2-90=0 | | 3.14+y=2 | | 5a+5b+5c= | | 4(2a-b)= | | f(-8)=36x+9x-7 | | a=23+4 | | 8x-25=3x-5 | | 4(3b-2a)= | | 13k+24=6k+6 | | f(-1)=25x-5x | | 5x+15=28x | | (17w-13)+(-6w+7)= | | .28x=700 | | x=-1.25y+3 | | 4.1x-17.49=2.6 | | (7w-13)+(-6w-7)= | | x-3=-1.25y | | f(-1)=4x-2x | | t+8t= | | f(2)=16x-2x | | 6x^2-84x+160=0 | | Y=-0.6(3)+0 |